Unveiling the heart of nursing: the transformative impact of emotional intelligence on patient-centred care - C. K. W. Gamage; W. S. Sudusinghe (Sri Lanka College of Internal Medicine, 2024)
The five-component model developed by Daniel Goleman serves as the primary description of emotional intelligence (EI). EI plays a significant role in the nursing profession by assisting students in acquiring traits including motivation, self-awareness, self-management, empathy, and interpersonal competence. Consequently, nurses equipped with heightened EI contribute to treatment that is both compassionate and highly collaborative. Positive impacts of EI on stress management, collaboration, and the promotion of personal and professional development have been linked to higher levels of job satisfaction. It also has a significant role in uniting healthcare workers from various backgrounds, which promotes improved communication and, eventually, improves patient care. Associations between increased levels of nurses' EI and improved interpersonal relationships, professional success, and a harmonious work-life balance emphasise the multifaceted advantages of EI in the nursing profession. Additionally, EI has a crucial role in influencing patient-nurse interactions, communication, trust, patient satisfaction, and overall outcomes. The integration of EI training into nursing education is essential, with a specific emphasis on the development of skills related to the identification, comprehension, and regulation of emotions. Continuing education and mentoring initiatives have the potential to further augment the EI of nurses. Improving healthcare outcomes and services requires an understanding of the importance of combining nursing practice and education.